2001
DOI: 10.1128/jvi.75.9.4239-4246.2001
|View full text |Cite
|
Sign up to set email alerts
|

Jaagsiekte Sheep Retrovirus Proviral Clone JSRV JS7 , Derived from the JS7 Lung Tumor Cell Line, Induces Ovine Pulmonary Carcinoma and Is Integrated into the Surfactant Protein A Gene

Abstract: Ovine pulmonary carcinoma (OPC) is a contagious neoplasm of alveolar epithelial type II (ATII) or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 34 publications
2
66
0
Order By: Relevance
“…OPA is a lung tumour derived from type II pneumocytes and Clara cells caused by an exogenous betaretrovirus known as jaagsiekte sheep retrovirus (JSRV) DeMartini et al, 2001). Most natural cases appear in animals aged 2-4 years and only when the tumour volume becomes sufficient to interfere with lung function, clinical signs can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…OPA is a lung tumour derived from type II pneumocytes and Clara cells caused by an exogenous betaretrovirus known as jaagsiekte sheep retrovirus (JSRV) DeMartini et al, 2001). Most natural cases appear in animals aged 2-4 years and only when the tumour volume becomes sufficient to interfere with lung function, clinical signs can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…This paradox highlights, once again, the multistep nature of tumorigenesis by JSRV in sheep; more importantly, it suggests other mechanisms, such as insertional mutagenesis, might also play a role in JSRV oncogenesis. Several groups have investigated the possibility that JSRV provirus may have common integration sites in the sheep genomes, and obtained interesting but inconsistent results (DeMartini et al, 2001;Cousens et al, 2004;Philbey et al, 2006). Notably, one common integration site was recently identified on the sheep chromosome 16 (Cousens et al, 2004), and another clonal integration was observed in the receptor protein tyrosine phosphatase g genes of chromosome 19 (Philbey et al, 2006).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…JSRV Env is a typical type-I transmembrane protein of approximately 620 amino acids in length before processing (York et al, 1992;Palmarini et al, 1999;DeMartini et al, 2001). The mature full-length Env is composed of surface (SU) and transmembrane (TM) subunits that are linked by disulfide bonds (Figure 1b).…”
Section: Sheep Retroviral Oncogenesis: a Historical Perspectivementioning
confidence: 99%
See 2 more Smart Citations